2007
DOI: 10.1002/qj.45
|View full text |Cite
|
Sign up to set email alerts
|

An objective definition of the Indian summer monsoon season and a new perspective on the ENSO–monsoon relationship

Abstract: ABSTRACT:The concept of an interannually varying Indian summer monsoon season is introduced here, considering that the duration of the primary driving of the Indian monsoon -the large-scale meridional gradient of the deep tropospheric heat source -may vary from one year to another. Onset (withdrawal) is defined as the day when the tropospheric heat source shifts from south to north (north to south). This physical principle leads to a new thermodynamic index of the seasonal mean monsoon. While the traditional m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
267
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 300 publications
(292 citation statements)
references
References 55 publications
(76 reference statements)
17
267
2
Order By: Relevance
“…Many studies have shown that warm SST anomalies are accompanied by large variations in the lower and upper troposphere due to enhanced latent heating aloft from convection over the ocean [33][34][35] . Furthermore, these changes are highly correlated with the strength of the monsoon circulation 31,34 . A more recent study using a coupled model framework also points out that a spatial extension of Indian Ocean warm pool could enhance the convection over the ocean while introducing a dry bias over land, by modulating the meridional Hadley circulation 36 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have shown that warm SST anomalies are accompanied by large variations in the lower and upper troposphere due to enhanced latent heating aloft from convection over the ocean [33][34][35] . Furthermore, these changes are highly correlated with the strength of the monsoon circulation 31,34 . A more recent study using a coupled model framework also points out that a spatial extension of Indian Ocean warm pool could enhance the convection over the ocean while introducing a dry bias over land, by modulating the meridional Hadley circulation 36 .…”
Section: Resultsmentioning
confidence: 99%
“…Once the monsoon rains set in on the South Asian subcontinent, the land surface cools down considerably. However, the troposphere above the land remains warm due to the latent heat release from the convective activity, keeping the thermal contrast functional 31 . This means that the tropospheric temperature is an ideal parameter for examining the thermodynamic forcing related to the monsoon 31 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used monsoon onset and withdrawal dates based on tropospheric temperatures by Goswami and Xavier [2005] and Xavier et al [2007]. For rainfall we used the gridded (1 Â 1 ) daily rainfall data over India developed by Rajeevan et al [2006].…”
Section: Datamentioning
confidence: 99%
“…These periods contain nearly all observed onset and withdrawal dates of monsoons defined in different ways [e.g., Ananthakrishnan and Soman, 1989;Fasullo and Webster, 2003;Goswami and Xavier, 2005;Joseph et al, 2006;Pai and Nair, 2009;Prasad and Hayashi, 2005;Taniguchi and Koike, 2006;Wang et al, 2004;Xavier et al, 2007;Zhang et al, 2002]. To consider forecasting of early and late season rainfall, which may be as important for crop yields and water resources as the total monsoon rainfall, we exploit two aspects of global climate with obvious connections to the Indian monsoon, local heating over the Indian subcontinent and its surroundings and the El Niño-Southern Oscillation, which correlate with onset and withdrawal dates [Goswami and Xavier, 2005;Rajagopalan and Molnar, 2012;Xavier et al, 2007]. Although Singh et al [2014] recently showed correlations between monthly rainfall variability and concurrent Pacific and Indian Ocean forcings that could potentially be exploited for improving skill, we found virtually no predictability of the peak monsoon season (mid-June to midAugust) rainfall with any of these large-scale climate features, but some success with the early and late seasons.…”
Section: Introductionmentioning
confidence: 99%